The Impact of the SARS-CoV-2 Pandemic on Stress and Anxiety of Dental Students - Zenthöfer, Andreas; Graf, Andreas; Rammelsberg, Peter; Klotz, Anna-Luisa (European Journal of Dentistry, 2023)
Objectives To investigate the impact of the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic on stress and anxiety of preclinical and clinical dental students.Materials and Methods Dental students (participants) in their clinical course (CC; n = 64) or preclinical course (PCC; n = 53) were included in the study. The subjective perceived levels of stress and anxiety were evaluated using the Dental Environment Stress (DES) questionnaire and the Depression, Anxiety and Stress Scales (DASS) questionnaire. Cortisol levels were measured in saliva samples collected from participants. Knowledge of the pandemic was evaluated using a 100-mm visual analog scale. All data were collected twice: once during the university holidays and once during term time.Statistical Analysis Results from DES, DASS, and salivary cortisol tests were compared between baseline and follow-up using descriptive and bivariate statistics. Multivariate linear regression models were computed with DES, DASS, and cortisol values as dependent variables to analyze possible influencing factors.Results Participants showed medium levels of stress and anxiety at baseline and follow-up. The DASS score in the “anxiety” subdomain was significantly higher in the PCC group than in the CC group at baseline (p < 0.001) and increased during term time. DASS scores in the “stress” subdomain also increased during term time. However, both subdomain scores were lower than the cutoff value for a psychological disorder. The mean total DES scores were 615.9 ± 97.7 in the CC group and 580.40 ± 98.9 in the PCC group. These scores indicated medium stress levels and were not significantly different between the groups, nor did they change during the study period. Mean saliva cortisol levels were higher in the CC group (9.2 ± 5.2) than in the PCC group (4.9 ± 2.2) at baseline (p < 0.001) but converged by follow-up. Multivariate regression models showed that intraindividual perception of stress at baseline was consistently the most important aspect for changes in stress and anxiety levels during term time. The SARS-CoV-2 pandemic affected stress and anxiety levels in some participants, but this was not ubiquitous.Conclusion Intraindividual differences in stress perception seem to be more relevant than course affiliation (preclinical or clinical) or the SARS-CoV-2 pandemic to stress and anxiety levels in dental students.
Keywords: stress; dentistry students; COVID-19